2010
DOI: 10.1002/mnfr.200900409
|View full text |Cite
|
Sign up to set email alerts
|

6‐Shogaol is more effective than 6‐gingerol and curcumin in inhibiting 12‐O‐tetradecanoylphorbol 13‐acetate‐induced tumor promotion in mice

Abstract: We previously reported that 6-shogaol strongly suppressed lipopolysaccharide-induced overexpression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in murine macrophages. In this study, we further compared curcumin, 6-gingerol, and 6-shogaol's molecular mechanism of action and their anti-tumor properties. We demonstrate that topical application of 6-shogaol more effectively inhibited 12-O-tetradecanoylphorbol 13-acetate (TPA)-stimulated transcription of iNOS and COX-2 mRNA expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
75
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 38 publications
10
75
0
Order By: Relevance
“…Kim et al (2008) (Sang et al, 2009). Along with our collaborators, we have reported that [6]-shogaol was more effective than [6]-gingerol in inhibiting 12-O-tetradecanoylphorbol-13-acetate-induced tumor promotion in mice (Wu et al, 2010). Furthermore, Dugasani et al (2010) The pharmacokinetics of [6]-shogaol in mice and in humans have been investigated (Zick et al, 2008(Zick et al, , 2010Wang et al, 2009;Asami et al, 2010;Iwabu et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Kim et al (2008) (Sang et al, 2009). Along with our collaborators, we have reported that [6]-shogaol was more effective than [6]-gingerol in inhibiting 12-O-tetradecanoylphorbol-13-acetate-induced tumor promotion in mice (Wu et al, 2010). Furthermore, Dugasani et al (2010) The pharmacokinetics of [6]-shogaol in mice and in humans have been investigated (Zick et al, 2008(Zick et al, , 2010Wang et al, 2009;Asami et al, 2010;Iwabu et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that shogaols are minor components in fresh ginger, and the ratio of [6]-shogaol to [6]-gingerol is approximately 1:1 in dried ginger (Govindarajan, 1982a,b;Sang et al, 2009;Wu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Gingerols (especially 6-gingerol) are the major components in the fresh ginger rhizome. The amount of shogaols is increased in the dried ginger, as evidenced by the reduction of the ratio of 6-gingerol to 6-shogaol from 10:1 in fresh ginger to 1:1 in dried ginger (17,18,20).…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for the treatment of migraine headaches, muscular aches, pains, sore throats, common cold, fl u-like symptoms, indigestion and even painful menstrual periods (Dugasani et al, 2010;El-Ghorab et al, 2010). Moreover, ginger contains phenolic compounds such as gingerols, zingerone and shogaols, which possess antioxidant, anti-infl ammatory and anticancer properties (Stoilova et al, 2007;Chen et al, 2008;Dugasani et al, 2010;Wu et al, 2010). Kaur and Kapoor (2002) determined the total phenolic content (TPC) of 36 vegetables in Asia including ginger.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TPC and antioxidant activity of ginger increased a er drying (Puengphian and Sirichote, 2008). This is due to the conversion of 6-gingerol, which is the most abundant component in the fresh ginger rhizome, to 6-shogaol during drying (Balladin et al, 1996;Ali et al, 2008;Wu et al, 2010). Dugasani et al (2010) reported that 6-shogaol has exhibited more potent antioxidant properties than gingerols; the scavenging potential was in the order of 6-shogaol > 10-gingerol > 8-gingerol > 6-gingerol.…”
Section: Introductionmentioning
confidence: 99%